Conservation of "Paluma" guavas coated with cassava starch and pectin (2018)
This study was to evaluate the post-harvest conservation of "Paluma" guavas coated with cassava starch and pectin. The selected and disinfected fruit samples were coated with cassava starch or pectin at concentrations of 0 (control), 2, 4 and 6%. Then, fruits were stored at room temperature (25 ± 1.0°C) for 12 days. Every three days, evaluations of mass loss, length, diameter, color of peel and pulp, pulp firmness, total soluble solids, pH and vitamin C content were held. The experiment was completely randomized in a 4 x 5 factorial design with four concentrations of the solutions and five storage periods with three replications. The results showed that cassava starch and pectin-based coatings can be an alternative for maintaining the post-harvest quality of "Paluma" guavas. Concentrations of 4 and 6% of both types of coating provided good results regarding the retention of some attributes. The cassava starch kept the fruits brighter compared to fruits coated with pectin.